2021
DOI: 10.5802/crgeos.55
|View full text |Cite
|
Sign up to set email alerts
|

Impact of integration time steps of rain drop size distribution on their structuring and their modelling: a case study in northern Benin

Abstract: Impact of integration time steps of rain drop size distribution on their structuring and their modelling: a case study in northern Benin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In West Africa, gamma and lognormal DSD models are used more to adjust measured DSDs [Nzeukou et al, 2004, Ochou et al, 2007, Sauvageot and Lacaux, 1995, Moumouni et al, 2008, 2021. This study showed that these models are well adapted for the analyzed DSDs, but the generalized gamma DSD model is better because of its flexibility [Lee et al, 2004].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In West Africa, gamma and lognormal DSD models are used more to adjust measured DSDs [Nzeukou et al, 2004, Ochou et al, 2007, Sauvageot and Lacaux, 1995, Moumouni et al, 2008, 2021. This study showed that these models are well adapted for the analyzed DSDs, but the generalized gamma DSD model is better because of its flexibility [Lee et al, 2004].…”
Section: Discussionmentioning
confidence: 95%
“…From these data, Moumouni et al [2021] computed other rain DSDs datasets of various integration time steps ( , 2, 3, 4, . .…”
Section: Datasetsmentioning
confidence: 99%
See 3 more Smart Citations